Turn-Taking Patterns in the Characters’ Dialogue in The Help (2011) Movie - Rifati Hanifa (Passage, 2019)
This study aims to examine the turn-taking patterns and the possible factors influencing turn-taking in The Help (2011) movie. Particular conversations were used as the data, namely the conversations between Miss Celia and Minny (M1) as well as the conversation between Miss Hilly and Minny (M2). Using the turn-taking theory from Levinson (1983) as set out by Sacks, Schegloff, and Jefferson (1974), this study found three turn-taking patterns that occurred in both conversations; they are self-selection (SS), current speaker selects the next speaker (CS2TNS), and current speaker continues (CSC). Factors influencing turn-taking were also found in the conversations; they are social status and discourse topic. Regarding the turn-taking patterns, self-selection (SS) is the most common pattern that emerged in M1, meanwhile current speaker selects the next speaker (CS2TNS) is the dominant used in M2. The use of SS in M1 indicates that the participants have a close relationship which is portrayed through the topic being discussed. On the contrary, in M2, CS2TNS which occurs mostly in the form of command shows the power of the maid’s master. This suggests that the use of CS2TNS pattern is mostly influenced by social status. Keywords: Conversation Analysis, Turn-Taking Patterns, Factors of Turn-Taking